2022
DOI: 10.1186/s12864-022-08618-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis and expression profiles of TCP gene family in Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn.) revealed the potential function of FtTCP15 and FtTCP18 in response to abiotic stress

Abstract: Background As transcription factors, the TCP genes are considered to be promising targets for crop enhancement for their responses to abiotic stresses. However, information on the systematic characterization and functional expression profiles under abiotic stress of TCPs in Tartary buckwheat (Fagopyrum tataricum (L.) Gaertn.) is limited. Results In this study, we identified 26 FtTCPs and named them according to their position on the chromosomes. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Duplication event researches have shown that segmental duplications are the main driving force for expansion and evolution of the TCP gene family ( Cannon et al, 2004 ; Wang et al, 2012 ). In support to these findings, research in Tartary buckwheat ( Yang M. et al, 2022 ), and M. acuminata ( Wang J. et al, 2022 ) have shown that the segmental duplication was responsible for the expansion of TCP gene family, and that the TCP gene family has undergone three WGDs during evolution. Therefore, to further understand the gene duplication events of TCP members in 17 different plant species, we computed for duplication event types using the plant duplicate gene database, PDGD ( http://pdgd.njau.edu.cn8080 ) ( Lee et al, 2012 ) ( Figure 5 ).…”
Section: Tcp Gene Family Duplication Eventsmentioning
confidence: 83%
“…Duplication event researches have shown that segmental duplications are the main driving force for expansion and evolution of the TCP gene family ( Cannon et al, 2004 ; Wang et al, 2012 ). In support to these findings, research in Tartary buckwheat ( Yang M. et al, 2022 ), and M. acuminata ( Wang J. et al, 2022 ) have shown that the segmental duplication was responsible for the expansion of TCP gene family, and that the TCP gene family has undergone three WGDs during evolution. Therefore, to further understand the gene duplication events of TCP members in 17 different plant species, we computed for duplication event types using the plant duplicate gene database, PDGD ( http://pdgd.njau.edu.cn8080 ) ( Lee et al, 2012 ) ( Figure 5 ).…”
Section: Tcp Gene Family Duplication Eventsmentioning
confidence: 83%
“…Cis-acting regulatory elements (CAREs) control the precise initiation and transcription efficiency of gene transcription by binding to transcription factors ( Yang et al., 2022 ). This study extracted the upstream regions 2,000 bp of D. nobile TCP genes to identify putative CAREs and investigate their functions.…”
Section: Resultsmentioning
confidence: 99%
“…Since transcription factors regulate the transcription of target genes within the nucleus, DnTCPs are likely to be localized in the nucleus. Some studies have analyzed the subcellular localization of Class I TCPs ( Jin et al., 2022 ; Yang et al., 2022 ; Ren et al., 2023 ). In this study, Class I TCPs, especially DnTCP9 and DnTCP18, were selected to investigate their subcellular localization, which could have unique roles in perianth development via binding to specific MADS-box.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that TFs that are highly or specifically expressed in seeds are the best candidates for regulating SS genes. To date, 17 TF families with 1075 genes have been identified in the TBG (J. Li et al., 2022; Liu et al., 2018; Liu, Fu, et al., 2019; Liu, Huang, Ma, et al., 2019; Liu, Huang, Sun, et al., 2019; Liu, Ma, et al., 2019; Liu, Sun, Ma, Huang, et al., 2019; Liu, Sun, Ma, Zheng, et al., 2019; Liu, Wang, et al., 2019; Liu, Wen, et al., 2019; Ma et al., 2019; W. Sun, Jin, Ma, Chen, & Liu, 2020; W. Sun, Ma, Chen, & Liu, 2020; Yan et al., 2021; Yang et al., 2022; Zhao et al., 2021). Unexpectedly, most TFs were not expressed in the Tartary buckwheat seeds after we analyzed their expression patterns in the roots, stems, leaves, flowers, and fruits based on the TBD.…”
Section: Resultsmentioning
confidence: 99%